2016
DOI: 10.1089/wound.2014.0544
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaEmbryos as a Model for Wound-Induced Transcriptional Dynamics: Genetic Strategies to Achieve a Localized Wound Response

Abstract: While many studies have established a paradigm for tissue repair at the level of cellular remodeling, it is not clear how an organism restricts a response only to the injured region of a damaged tissue. Skin, the largest organ in the human body, is prone to injury, and repair of epidermal tissue represents a medically relevant system to investigate. Studies in provide a robust genetic system to identify molecular components that will positively impact repair and healing. The skin consists of a single-cell epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Compensatory proliferation and growth occur in wing imaginal discs, where cell death by irradiation, microsurgery, fragmentation or genetic means, leads to regeneration and development of intact adult structures (Haynie and Bryant ; Huh et al, ; Pérez‐Garijo et al, ; Bergantinos et al, ). As well as wing disc injury (Díaz‐García and Baonza, ), adult epithelial injury (Rämet et al, ) and embryonic dorsal closure (Noselli and Agnès, ) are also used to investigate wound closure, successfully providing cellular and genetic insights relevant to vertebrates (Juarez, ). The gut is used to study injury responses of intestinal stem cells, regulated by intrinsic signals, and extrinsic niche signals for self‐replication (Jiang et al, ).…”
Section: Drosophila Comes Of Age As a Model Organism To Investigate Rmentioning
confidence: 99%
“…Compensatory proliferation and growth occur in wing imaginal discs, where cell death by irradiation, microsurgery, fragmentation or genetic means, leads to regeneration and development of intact adult structures (Haynie and Bryant ; Huh et al, ; Pérez‐Garijo et al, ; Bergantinos et al, ). As well as wing disc injury (Díaz‐García and Baonza, ), adult epithelial injury (Rämet et al, ) and embryonic dorsal closure (Noselli and Agnès, ) are also used to investigate wound closure, successfully providing cellular and genetic insights relevant to vertebrates (Juarez, ). The gut is used to study injury responses of intestinal stem cells, regulated by intrinsic signals, and extrinsic niche signals for self‐replication (Jiang et al, ).…”
Section: Drosophila Comes Of Age As a Model Organism To Investigate Rmentioning
confidence: 99%
“…In Drosophila the Duox gene is also required for activation of wound response genes in epidermal cells (25). Our previous studies have shown that Duox and hydrogen peroxide act upstream of serine protease(s) for the wound-dependent activation of the ple and Ddc genes (26).…”
Section: Extracellular Regulation Of Epidermal Wound Transcription Bymentioning
confidence: 99%
“…It has been applied to three different data sets of confocal images (each data set contains several images to represent only one sample of a tissue) taken from the model organism, Drosophila melanogaster: salivary glands, embryos and egg chambers. Classically, all of them have been widely used to analyse the different biological events in which epithelial cells are involved: division, migration, apoptosis, differentiation, polarity, cancer, wound healing and much more [33][34][35][36][37]. We consider that our present work has these novelties:…”
Section: Related Workmentioning
confidence: 99%